Semantic Analysis of the Meaning Sontoloyo politician In the Mr. Joko widodo Speech - Dede Irawan (Faktor Jurnal Ilmiah Kependidikan, 2020)
Semantic is a branch of linguistics that studies the meaning contained in a language, code, or another type of representation. In this research, the writer tries to analyze the semantic meaning of sontoloyo politician is conveyed by Mr. Joko widodo that use qualitative research design because this method is more focused on analyzing the meaning diction of sontoloyo politician which is expected to know core meaning and aim from this diction. The result of this research can be concluded that Sontoloyo politician has a connotative meaning, because the sontoloyo politician has meant that explain " the people who have political positions, political experts, and expert statesmen as like legislative, executive and judicial positions who have wrong behavior in carrying out their duties" in this statement has a communicative value and an expression based on intention must have conceptual content that not only includes physical characteristics, but also social and psychological.Semantic adalah cabang linguistik yang mempelajari makna yang terkandung dalam bahasa, kode, atau jenis representasi lainnya. Dalam penelitian ini penulis mencoba menganalisis makna semantik politisi sontoloyo yang disampaikan oleh Pak Joko Widodo yang menggunakan desain penelitian kualitatif, karena metode ini lebih fokus pada analisis makna diksi politisi sontoloyo yang diharapkan mengetahui makna inti dan tujuan dari diksi tersebut. Hasil penelitian ini dapat disimpulkan bahwa politisi Sontoloyo memiliki makna konotatif, karena politisi sontoloyo memiliki makna yang menjelaskan “orang-orang yang memiliki posisi politik, pakar politik, dan pakar negarawan seperti posisi legislatif, eksekutif dan yudikatif yang memiliki perilaku salah dalam menjalankan tugasnya ”dalam pernyataan ini memiliki nilai komunikatif dan ekspresi berdasarkan pada konten konseptual murni dan tidak hanya mencakup karakteristik fisik, tetapi juga properti sosial dan psikologis. Key Words: Semantic Analysis and Sontoloyo Politician